The Blessings of Books - Gordon, Michael (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2023)
The attack on the written word is not new. It has happened many times through history, especially in modern times as the availability of books has grown so rapidly. It is most often in authoritarian regimes that books are deemed a potential threat, and the elimination of this threat a means to maintain control of a potentially rebellious population. Probably the most heinous of book banning and burnings occurred during Nazi rule, prior to and during the Second World War. To witness, recently, in the United States the ugly head book banning and their removal from libraries is a sad commentary on the state of some senior politicians, including Governors and Judicial leaders. Fortunately, there is vigorous opposition to these efforts and notable successes in the quest for universal access to the world of books.